Response of two breeds of chickens to Ascaridia galli infections from two geographic sources - Abdelqader, A.; Gauly, M.; Wollny, C.B.A. (Elsevier, 2007)
Comparative resistance to different isolates of Ascaridia galli was investigated in a local chicken breed from Jordan (LC) and in the Lohmann LSL white chicken (LW) strain. In two trials, birds of LC and LW were inoculated orally at 1-day old with 250 embryonated A. galli eggs. In the first trial a German source of A. galli was used, whereas in the second trial, a Jordan source of A. galli was used. At week 7 of infection, infected LC birds harbored significantly (P < 0.05) fewer worms and excreted less A. galli eggs than infected LW birds. A. galli isolated from Jordan were less infectious than A. galli from Germany. Results suggest that the variation in genetic background between LC and LW is involved in the resistance to A. galli infection. A. galli isolates from different geographic areas differ in their ability to infect different chicken genotypes.